Two interpretations of human evolution: Essentialism and Darwinism - Henneberg, Maciej (Anthropological Review, 2009)
Despite intensive studies of a large number of fossils discovered during the 20th century there is no consensus as to the interpretation of the process of hominin evolution. Some authors see as many as six genera and some 17 species, while others argue for a single lineage from Plio/Pleistocene until today. Such diversity of interpretations of the same facts indicates lack of a uniform theoretical basis underlying studies of human evolution. Debates can be resolved using basic principles of scientific inquiry - parsimony and falsification of null hypotheses. Hypothesis testing is now possible with respect to the evolution of basic hominin characteristics such as brain size, body size and the size of the dentition that have sample sizes of a few hundred individual data points each. These characters display a continuous change with time. Analyses of variance do not falsify the null hypothesis of the existence of only one species at any time - variances around regression lines on time do not differ from the variance observed in the single species of Homo sapiens - distributions of residuals are normal. Thus, splitting of the hominin lineage into coeval species can only be based on descriptive characteristics that are liable to errors of subjective judgment.